The management of life skills program for students with disabilities - Widia Murni Wijaya; Liah Siti Syarifah (Institute of Advanced Engineering and Science, 2022)
This study aimed to explore the management of the life skills program organized by special high schools at the senior level. The case study approach was carried out by employing observations, interviews, and documentation techniques. The participants involved principal, teachers, graduates, parents, local government, and company. These participants involved themselves in efforts to support actively and their commitment to the success of the management of life skills program. The results indicated that the life skills program was well managed as it successfully delivered graduates to work in the company and be financially independent. The commitment of the school with the company and parents to enhance the independence of graduates with disabilities was through the life skills program to provide them with some valuable skills.